2018
DOI: 10.1007/s11912-018-0697-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination Immunotherapy in Non-small Cell Lung Cancer

Abstract: Clinical trials evaluating combination PD-1 and CTLA-4 blockade as well as PD-1 in combination with agents targeting IDO1, B7-H3, VEGF, and EGFR show promising results. Additional studies targeting other immune pathways like TIGIT, LAG-3, and cellular therapies are ongoing. Combination immunotherapy has the potential to improve outcomes in NSCLC. Data from early clinical trials is promising and reveals that these agents can be administered together safely without a significant increase in toxicity. Further stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 59 publications
1
24
0
1
Order By: Relevance
“…Recent evidence demonstrates that B7-H3-expressing NSCLC escapes antitumor immunity via CD8 + T-cell repression despite anti-PD-1 immunotherapy and that B7-H3 blockade, especially in combination with the PD-1 blockade, exhibits potent antitumor efficacy mediated by increased number of tumor-specific CD8 + T cells [ 22 ]. This study represented a novel and promising therapeutic strategy against B7-H3-expressing tumors [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence demonstrates that B7-H3-expressing NSCLC escapes antitumor immunity via CD8 + T-cell repression despite anti-PD-1 immunotherapy and that B7-H3 blockade, especially in combination with the PD-1 blockade, exhibits potent antitumor efficacy mediated by increased number of tumor-specific CD8 + T cells [ 22 ]. This study represented a novel and promising therapeutic strategy against B7-H3-expressing tumors [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…B7-H3 (CD276) belongs to a family of immune modulators that also includes PD-L1 (also known as B7-H1) [ 19 , 20 , 21 ]. Recent evidence demonstrates that B7-H3 blockade, especially when combined with an anti-PD-1 blockade, is a promising strategy for the treatment of B7-H3-expressing NSCLCs that are refractory to anti-PD-1 therapy [ 22 ], making B7-H3 a promising molecular target [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, the association of B7-H3 expression with survival in patients with pancreatic cancer remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that angiogenic factors are immunosuppressive, implying that a combination of immune checkpoint blockade with antiangiogenic agents may exhibit synergistic antitumor activity in NSCLC treatments. Indeed, primary data from clinical trials in combination therapy with immune checkpoint blockade (nivolumab and pembrolizumab) and antiangiogenic agents (bevacizumab, ramucirumab, and nintedanib) show promising results for NSCLC [ 60 ]. For example, the phase I trial ( NCT01454102 ) evaluated the efficacy and safety of combination maintenance treatment of nivolumab with bevacizumab in advanced NSCLC patients with response to first-line platinum-based chemotherapy.…”
Section: Anti-pd-1/pd-l1-based Combinatory Therapies For Nsclc Trementioning
confidence: 99%
“…Furthermore, most NSCLC patients do not respond to immune checkpoint inhibitor monotherapy (8,9). Multiple combination modalities, including agents targeting EGFR, ALK, immune checkpoints and/or immunosuppressive tumor microenvironment, and chemotherapy are being tested; however, the longterm risks and benefits of these strategies in the treatment of NSCLC are currently unknown (10,11). A better understanding of the mechanisms regulating EGFR expression and activity will advance the biology of na€ ve tumors, and inform rational strategies for the personalized, multimodality management of aggressive NSCLC.…”
Section: Introductionmentioning
confidence: 99%